STUDENTS’ ERRORS IN TRANSLATING NARRATIVE TEXT BASED ON DULAY’S SURFACE STRATEGY TAXONOMY - Dwi Handayani; Fahri Haswani (Universitas Negeri Medan, 2018)
This study is purposed to find out the errors in translating narrative text based on Dulay‟s Surface Strategy taxonomy. In addition, this study is also aimed to describe the possible causes of those errors. This study applied the descriptive qualitative research which the data were obtained from the translation texts that were written by the second- year students of SMA Tunas Pelita Binjai. The data were collected by using the students‟ translation text. Then the data were analyzed by identifying the errors, describing the errors, and the last explaining the errors. The errors that occurred in students‟ translation texts are omission error, addition error, misformation error, and misordering error. The result of the research indicates that the students made 230 errors which classified into: 22,61% omission error, 11,30% addition error, 65,22% misformation error, and 0,87% misordering error. The most dominant error that occurred in the students‟ translation text is misformation errors and the causes of errors were influenced by the interlingual transfer and intralingual transfer.